Idias of Khushal Khan Khattak About Women in “Dastaarna” - Ahmad, Mazhar; Gul, Laila; Rahman, Inayat Ur (sourcecoder, 2023)
Khushal Khan Khattak is known as the most versatile figure in Pashto literature. Khushal Khan was a poet and a writer. Khushal Khan Khattak, during his imprisonment in the Fort of Ranthambhore (India) wrote a book “Dastarnama” such a complete and useful book on aptitude. In this book, Khushal Khan Khattak has also called dastar as a sign of a man's modesty and honor. This paper examines all of Khushal's ideas regarding the "Manual" that he holds about a woman.